The loss of investiture. Assay of comparative lawbetween Colombia and France - Bernal-Gómez, Daniel Rigoberto (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article aims to show how the concept of loss of investiture was built in Colombian law, and similarly, how French law handles this figure, with the intention of achieving a better understanding of th is institution, which from the perspective of the democracy, ensures that there is a level of transparency in the management of those who have the duty to represent their voters.